Biogenic volatile organic compounds dominated the near-surface ozone generation in Sichuan Basin, China, during fall and wintertime - Dasheng Huang; Qing Li; Yan Han; Shi-Yong Xia; Jiawei Zhou; Hanxiong Che; Keding Lu; Fumo Yang; Xin Long; Yang Chen (Journal of Environmental Sciences, 2024)

Springtime reactive volatile organic compounds (VOCs) and impacts on ozone in urban areas of Yunnan-Guizhou plateau, China: A PTR-TOF-MS study - Qing Li; Yan Han; Dasheng Huang; Jiawei Zhou; Hanxiong Che; Liuyi Zhang; Keding Lu; Fumo Yang; Yang Chen (Atmospheric Environment, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Portable high-throughput multimodal immunoassay platform for rapid on-site COVID-19 diagnostics - Yanke Shan; Bin Wang; Huachuan Huang; Keding Yan; Wenzhi Li; Shouyu Wang; Fei Liu (Analytica Chimica Acta, 2023)